2021
DOI: 10.4269/ajtmh.21-0086
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Artemether-Lumefantrine for the Treatment of Plasmodium falciparum Malaria in Bohicon and Kandi, Republic of Benin, 2018–2019

Abstract: In 2005, artemether-lumefantrine (AL), an artemisinin-based combination therapy, was introduced as the first-line treatment of uncomplicated Plasmodium falciparum malaria in Benin. Per World Health Organization recommendations to monitor the efficacy of antimalarial treatment, we conducted a therapeutic efficacy study with AL for uncomplicated P. falciparum malaria in Bohicon and Kandi, Benin, from 2018 to 2019. Febrile patients aged 6 to 59 months with confirmed P. falciparum monoinfection received supervised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The study also assessed, for the first time, the efficacy of DP, a second-line treatment introduced in 2016, and demonstrated high efficacy (PCR corrected cure rates of 100% in Kouvé and Anié on day 28 and 98.9% in Kouvé and 100% in Anié on day 42, respectively). These results are similar to those reported in neighboring countries such as Ghana [ 45 ] and Benin [ 46 ], but also as well as other West African countries [ 47 54 ], and Central and East African countries [ 55 – 57 ]. This contrasts with recent reports of the reduced PCR-corrected cure rates of AL (< 90%) found, in the absence of a Pfkelch13 validated variants, in Burkina Faso [ 58 ], Angola [ 59 ], and the Democratic Republic of Congo [ 60 ], suggesting lumefantrine resistance.…”
Section: Discussionsupporting
confidence: 90%
“…The study also assessed, for the first time, the efficacy of DP, a second-line treatment introduced in 2016, and demonstrated high efficacy (PCR corrected cure rates of 100% in Kouvé and Anié on day 28 and 98.9% in Kouvé and 100% in Anié on day 42, respectively). These results are similar to those reported in neighboring countries such as Ghana [ 45 ] and Benin [ 46 ], but also as well as other West African countries [ 47 54 ], and Central and East African countries [ 55 – 57 ]. This contrasts with recent reports of the reduced PCR-corrected cure rates of AL (< 90%) found, in the absence of a Pfkelch13 validated variants, in Burkina Faso [ 58 ], Angola [ 59 ], and the Democratic Republic of Congo [ 60 ], suggesting lumefantrine resistance.…”
Section: Discussionsupporting
confidence: 90%
“…All three study sites demonstrated an AL efficacy of over the WHO threshold, with ACPRs in Agadez, Tessaoua, and Gaya of 97.05%, 98.87% and 92.18%, respectively. Several studies have evaluated the efficacy of AL in Niger and the sub region and have demonstrated its continued efficacy in West Africa: 91% efficacy in Sélingué, Mali in 2015 [ 20 ], 96.7% and 96.3% efficacy in Bohicon and Kandi, Benin, respectively, in 2018 [ 21 ], 98.8% efficacy in Kédougou, Senegal, in 2018 [ 22 ] and 98.8% efficacy in Abidjan, Côte d’Ivoire, in 2016 [ 23 ]. In addition to its efficacy, this molecule is well tolerated by patients and no adverse events were reported during the study.…”
Section: Discussionmentioning
confidence: 99%